Pelatihan Perbanyakan Tanaman Hias Secara Vegetatif - Siti Nurul Iftitah; Mardjono, Robiul Fitri Masithoh; Diesyana Ajeng Pramesti; Basri (CARADDE: Jurnal Pengabdian Kepada Masyarakat, 2021)
Plant propagation training conducted for partners, namely mothers (women’s empowerment) aims to provide insights and skills for partners so that they can carry out and develop plant propagation properly. The technique of vegetative propagation is by means of cuttings, grafting and grafting. The method used consists of 3 stages, namely socialization, training / practice and mentoring. The results of the activity showed that there was an increase in knowledge and skills in the cultivation and propagation of ornamental plants in a good vegetative manner, so that it was hoped that it could increase the diversity of colors from plant propagation. From this activity, it can be concluded that there has been a change in the knowledge and skills of partners, namely partners are able to properly cultivate ornamental plants, starting from preparing planting media or land, planting, and maintaining plants. In addition, partners can also propagate ornamental plants vegetatively and successfully.